Effect of Palliative Care-Led Meetings for Families of Patients With Chronic Critical Illness: A Randomized Clinical Trial - Carson, Shannon S; Cox, Christopher E; Wallenstein, Sylvan; Hanson, Laura C; Danis, Marion; Tulsky, James A; Chai, Emily; Nelson, Judith E (JAMA : the journal of the American Medical Association, 2016)
Family caregivers of patients with chronic critical illness experience significant psychological distress. To determine whether family informational and emotional support meetings led by palliative care clinicians improve family anxiety and depression. A multicenter randomized clinical trial conducted from October 2010 through November 2014 in 4 medical intensive care units (ICUs). Adult patients (aged ≥21 years) requiring 7 days of mechanical ventilation were randomized and their family surrogate decision makers were enrolled in the study. Observers were blinded to group allocation for the measurement of the primary outcomes. At least 2 structured family meetings led by palliative care specialists and provision of an informational brochure (intervention) compared with provision of an informational brochure and routine family meetings conducted by ICU teams (control). There were 130 patients with 184 family surrogate decision makers in the intervention group and 126 patients with 181 family surrogate decision makers in the control group. The primary outcome was Hospital Anxiety and Depression Scale symptom score (HADS; score range, 0 [best] to 42 [worst]; minimal clinically important difference, 1.5) obtained during 3-month follow-up interviews with the surrogate decision makers. Secondary outcomes included posttraumatic stress disorder experienced by the family and measured by the Impact of Events Scale-Revised (IES-R; total score range, 0 [best] to 88 [worst]), discussion of patient preferences, hospital length of stay, and 90-day survival. Among 365 family surrogate decision makers (mean age, 51 years; 71% female), 312 completed the study. At 3 months, there was no significant difference in anxiety and depression symptoms between surrogate decision makers in the intervention group and the control group (adjusted mean HADS score, 12.2 vs 11.4, respectively; between-group difference, 0.8 [95% CI, -0.9 to 2.6]; P = .34). Posttraumatic stress disorder symptoms were higher in the intervention group (adjusted mean IES-R score, 25.9) compared with the control group (adjusted mean IES-R score, 21.3) (between-group difference, 4.60 [95% CI, 0.01 to 9.10]; P = .0495). There was no difference between groups regarding the discussion of patient preferences (intervention, 75%; control, 83%; odds ratio, 0.63 [95% CI, 0.34 to 1.16; P = .14]). The median number of hospital days for patients in the intervention vs the control group (19 days vs 23 days, respectively; between-group difference, -4 days [95% CI, -6 to 3 days]; P = .51) and 90-day survival (hazard ratio, 0.95 [95% CI, 0.65 to 1.38], P = .96) were not significantly different. Among families of patients with chronic critical illness, the use of palliative care-led informational and emotional support meetings compared with usual care did not reduce anxiety or depression symptoms and may have increased posttraumatic stress disorder symptoms. These findings do not support routine or mandatory palliative care-led discussion of goals of care for all families of patients with chronic critical illness. clinicaltrials.gov Identifier: NCT01230099.